Social preferences : an introduction to behavioural economics and experimental research - Drouvelis, Michalis (Agenda Publishing, 2021)
This introduction to one of the key areas of behavioural economics - social preferences - explains in clear, nontechnical language how particular groups of experiments have been used by behavioural economists to shed light on the processes of economic decision making. These include bargaining games, trust games and public good games. The significance of determinants such as punishment, sanctioning, emotion, cooperation, reciprocity, leadership, framing and cross-cultural differences are demonstrated and explained, and students are provided with the understanding and resources needed to replica.